Integration of Artificial Intelligence in Micro-patch Antenna Design for AMCA Aircraft - Divya, P.; Ganesh, R. Senthil; Sivakumar, S. A.; Vijayalakshmi, A.; Jabakumar, A. Kingsly; Shankar, B. Maruthi (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Artificial Intelligence (AI) can be utilized in various aspects of antenna design and optimization, including micro-patch antennas. Micro-patch antennas are compact, planar antennas that are widely used in wireless communication systems. AI techniques can enhance the performance of micro-patch antennas by optimizing their design, improving their efficiency, and reducing their size. This paper describes the development of low-cost networked model Aircraft, simulations used to demonstrate two application areas providing the Unmanned Aerial Vehicle (UAV) and enhanced bandwidth using the Micro-patch antenna at the receiver side of the model. The existing method has only 4 channel transmitter, but the proposed system is designed using 6 channel transmitter at the Transmitter side to improve transmission efficiency. The bandwidth from the previous model is 6.35% with return loss of 29dB and gain 8dB, it is enhanced to 14.81% with return loss of 32dB and gain 9.5dB. The HAL AMCA is one of the key components of Indian military industries. In this paper, a research effort is made using the project, HAL AMCA to develop fifth and sixth generation fighter aircraft for Indian air force and the Indian Navy for aviation safety and capacity with AI integrated micro-patch antenna design